2007
DOI: 10.15298/rusjtheriol.06.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Craniometrical characteristics of some Sorex araneus chromosomal races

Abstract: ABSTRACT. Skulls of 504 immature common shrews (Sorex araneus) representing seven chromosomal races (Moscow, Lepel, Manturovo, Yagry, Serov, Tomsk, and Neroosa) were examined using 24 morphometric variables and 15 indices derived from them. The races were found to differ in a number of dimensions and proportions of the skull. Each race has its own morphological appearance. Cluster analysis of craniometrical data showed that the Tomsk race was separated from other races. Factor analysis revealed the main trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, it has also been demonstrated (Chêtnicki et al, 1996;Polyakov et al, 2002;Okulova et al, 2004) that when the level of karyotype differentiation is higher, morphological differences between chromosome races of S. araneus become more visible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has also been demonstrated (Chêtnicki et al, 1996;Polyakov et al, 2002;Okulova et al, 2004) that when the level of karyotype differentiation is higher, morphological differences between chromosome races of S. araneus become more visible.…”
Section: Resultsmentioning
confidence: 99%
“…Intensive investigation of S. araneus karyology has revealed about 70 chromosome races in Europe and Siberia (Wójcik et al, 2002). The extent to which karyological and morphological differentiation coincide has been studied in different regions over the vast species range (Hausser, 1984;Zima & Král, 1985;Searle & Thorpe, 1987;Hausser et al, 1991;Meyer & Searle, 1994;Chêtnicki et al, 1996;Wójcik et al, 2000;Banaszek et al, 2002;Polyakov et al, 2002;Okulova et al, 2004). It has been demonstrated that differences in morphology do not conform to the geographical distribution of chromosome races of S. araneus (Zima & Král, 1985), and could be explained rather by differences in environmental conditions (Sulkava et al, 1985;Wójcik et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of researchers have found morphological differences between the chromosomal races of Sorex araneus (Chętnicki et al, 1996;Polyakov et al, 2002;Okulova et al, 2007), in most studies, morphometric variability was unassociated with racial boundaries (Sulkava et al, 1985;Searle & Thorpe, 1987;Wójcik et al, 2000;Banaszek et al, 2003;Mishta, 2007). Morphological difference was found in cases when the races differed in size.…”
Section: Discussionmentioning
confidence: 99%
“…Moska and Paśko (2006) found that though individuals of races from the same karyotypic group (Lęgunski Młyn and Popielno) do not clearly differ, canonical analysis and multidimensional scaling allow discrimination between hybrids and non-hybrids. Okulova et al (2007) found that several races differed in a number of dimensions and proportions of the skull. However, most authors did not find correspondence between membership in a chromosomal race and morphometric characteristics (Searle & Thorpe, 1987;Hausser, 1994;Meyer & Searle, 1994;Wójcik et al, 2000;Banaszek et al, 2003).…”
Section: Introductionmentioning
confidence: 99%